2022
DOI: 10.3390/w14132108
|View full text |Cite
|
Sign up to set email alerts
|

An Overview to Technical Solutions for Molybdenum Removal: Perspective from the Analysis of the Scientific Literature on Molybdenum and Drinking Water (1990–2019)

Abstract: A bibliometric analysis using the Scopus database was performed to investigate the research documents published from 1990 to 2019 in scientific sources related to molybdenum in drinking water and determine the quantitative characteristics of the research in this period. The results from the analysis revealed that the number of publications was maintained at a regular production of around 5 papers per year until 2009, followed by a fast linear increase in the production in the period from 2010 to 2016 (29 paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 127 publications
1
4
0
Order By: Relevance
“…The clear supremacy of articles when compared to other types of publications was totally consistent with the results mentioned by other authors who investigated the research published regarding water pollutants and treatment technologies [39,55,56]. However, the relatively high contribution of reviews is not so frequently reported, since the importance of the contributions in congress is significant in several engineering fields, including chemical, civil, and environmental [37,[57][58][59], although some examples with a higher relative importance of reviews over congress contributions can be found [36,60,61]. Therefore, the higher importance of reviews when compared to conference papers can be linked to topics with elevated numbers of documents published, which can be revised and summarized by the corresponding reviews.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The clear supremacy of articles when compared to other types of publications was totally consistent with the results mentioned by other authors who investigated the research published regarding water pollutants and treatment technologies [39,55,56]. However, the relatively high contribution of reviews is not so frequently reported, since the importance of the contributions in congress is significant in several engineering fields, including chemical, civil, and environmental [37,[57][58][59], although some examples with a higher relative importance of reviews over congress contributions can be found [36,60,61]. Therefore, the higher importance of reviews when compared to conference papers can be linked to topics with elevated numbers of documents published, which can be revised and summarized by the corresponding reviews.…”
Section: Resultssupporting
confidence: 86%
“…This approach enables access to relevant information and knowledge about the status of scientific research activities in specific disciplines, which helps researchers to identify novel schemes among the research [36]. Numerous bibliometric studies directly related to water pollution and wastewater treatment have been published [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum (Mo) is an essential microelement for humans, animals and plant life [1]. It is also widely used for different industrial applications such as high-speed tools, coating processes and metallurgy for improving alloys [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The average concentration of Mo in natural water reservoirs is normally 10 µg/L or less, but cases of significant excesses of this concentration (up to mg/L) are quite common [8]. The elevated Mo content in ecosystems is the result of anthropogenic activities such as mining and industrial activities associated with the production of alloys, catalysts, ceramics, lubricants and pigments [1,8]. In natural water reservoirs and industrial wastewater, Mo exists mainly in the form of Mo(VI) molybdate oxoanions.…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum, which is found as Mo(VI) in such wastewater and leachates, can be recovered via various methods [7,8], such as precipitation [9,10], adsorption [11,12] and solvent extraction [13,14]. Among the precipitation methods, sulphide precipitation is generally advantageous due to the lower solubility of metal sulphide precipitates, faster reaction rates, better settling properties and potential for selective metal removal and further valorisation of sulphide precipitates by smelting or hydrometallurgical treatment [15].…”
Section: Introductionmentioning
confidence: 99%